Protest and Ilmu Teluh: Superstitious Beliefs and Rituals in Thai Youth Political Movements - Sandhinera, Dhataratth (Journal of Arts and Thai Studies, 2025)
Background and Objectives: Between 2019 and 2023, Thailand witnessed waves of student- and youth-led protest movements. Although these young people are part of a new generation raised with scientific knowledge and technological advancements, many have chosen to incorporate supernatural beliefs and rituals—referred to as “ilmu teluh”—into their political activism, for example, the emergence of the “Ratsadon-muteluh”, a group which incorporates beliefs and rituals as a form of political expression. Methods: This research studies the social phenomenon of superstitious belief and ritual practice among youth protesters using three methods: documentary analysis, non-participatory observation, and in-depth interviews (secondary data). Results: Ilmu teluh rituals are practiced by numerous protest participants from various groups who believe that Thai society is dominated by a culture of privilege and oppression with a long-standing historical foundation, especially the Thai Royal Institution. These youth protesters perceive their political opponents, whom they label as the conservatives, to be highly credulous and devoted to superstition. As such, they therefore chose to use ilmu teluh as a symbolic tool to challenge their political opponents. Their protests targeted belief systems associated with prominent figures, while attempting to present an invented culture by reenacting rituals claimed to originate from the people instead. The protest rituals involving ilmu teluh were reenactments that did not follow the formal ritualistic principles of any particular belief system or religion, but were instead play-acting which comprises three acts: 1) the speech by protest leaders to clarify the objectives of the demonstration, 2) the role-playing as an artistic ritual to express emotions of resistance, and 3) the burning of effigies or objects as a form of symbolic communication through fire served as a climactic act in the performance. These rituals functioned both as a mechanism for moral healing and as a symbolic violence alternative to physical violence within the youth movements. Application of this study: This research offers a framework for understanding the use of ilmu teluh rituals as a form of symbolic resistance. It serves as an analytical tool for examining youth-led cultural movements and political expressions within the context of an authoritarian society. The study is relevant to scholars, activists, and policymakers seeking to understand movements driven by beliefs. Conclusions: Ilmu teluh rituals in Thai youth protests function as a symbolic expression that integrates political resistance with expressive culture. Through the reinterpretation and reconnection with traditional beliefs, youth protesters can use superstition as a tool for challenging authority, reclaiming public space, and expressing collective frustration. These rituals reflect a shift toward a movement rooted in the people rather than monopolized by the elites.